Feynman's tips on physics : reflections, advice, insights, practice : a problem-solving supplement to the Feynman lectures on physics - Feynman, Richard P. (Richard Phillips), 1918-1988 (Basic Books, 2013)
"With characteristic flair, insight, and humor, Feynman discusses topics physics students often struggle with and offers valuable tips on addressing them. Included here are three lectures on problem-solving and a lecture on inertial guidance omitted from The Feynman Lectures on Physics. An enlightening memoir by Matthew Sands and oral history interviews with Feynman and his Caltech colleagues provide firsthand accounts of the origins of Feynman's landmark lecture series"--P. [4] of cover.